2013
DOI: 10.1371/journal.pmed.1001536
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Quantitative PCR (Xpert MTB/RIF) for Tuberculous Meningitis in a High Burden Setting: A Prospective Study

Abstract: Vinod Patel and colleagues evaluate the sensitivity and specificity of quantitative PCR using Xpert MTB/RIF for diagnosis of TB meningitis in the high-burden setting of South Africa. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
144
3
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(175 citation statements)
references
References 37 publications
8
144
3
15
Order By: Relevance
“…In a predominantly HIV-infected SA TBM cohort study (87% of the 204 participants were HIV-infected), the sensitivity and specificity of Xpert were 67% and 94%, respectively; this analysis included patients with definite TBM (CSF M. tuberculosis culture and/or Amplicor PCR positive), compared with patients with other causes of meningitis as controls. [9] Although the overall sensitivity decreased to 36% when probable TBM was included in the reference standard, using a larger volume (3 mL) of centrifuged CSF compared with 1 mL of neat CSF increased the sensitivity markedly from 26% to 65% in this analysis.…”
Section: Definitive Diagnostic Methodsmentioning
confidence: 67%
“…In a predominantly HIV-infected SA TBM cohort study (87% of the 204 participants were HIV-infected), the sensitivity and specificity of Xpert were 67% and 94%, respectively; this analysis included patients with definite TBM (CSF M. tuberculosis culture and/or Amplicor PCR positive), compared with patients with other causes of meningitis as controls. [9] Although the overall sensitivity decreased to 36% when probable TBM was included in the reference standard, using a larger volume (3 mL) of centrifuged CSF compared with 1 mL of neat CSF increased the sensitivity markedly from 26% to 65% in this analysis.…”
Section: Definitive Diagnostic Methodsmentioning
confidence: 67%
“…Among participants without cryptococcal meningitis (who require large volume lumbar punctures for control of intracranial pressure), testing of at least 6 mL of CSF (median 10 mL [IQR [8][9][10][11][12]) was associated with a tuberculous meningitis diagnosis (19 [26%] of 73) compared with less than 6 mL (4 mL [3-5mL]; 3 [7%] of 43; p=0·014)].…”
Section: Resultsmentioning
confidence: 99%
“…Of the two major studies included in the meta-analysis, Patel and colleagues reported 67% sensitivity against microbiologically proven TBM and 36% against consensus clinical case definitions, while Nhu and colleagues showed 59% sensitivity against the same case definitions 1012 . Additionally, use of a larger volume of centrifuged CSF improves sensitivity of Xpert 10, 13 . Yet, inadequate negative predictive value means that Xpert cannot substitute for clinical judgement 14 .…”
Section: Introductionmentioning
confidence: 99%